Governance Beyond the State: Clientelism, Fiscal Populism, and Reform Challenges in Southeast Asian Democracies - Ningsih, Wening Mustika; Yusuf, Muhammad; Taufiqurokhman (Indonesian Scientific Publication, 2025)
This study investigates the pervasive role of informal political institutions in Southeast Asian governance, focusing on the entrenchment of clientelism, political dynasties, and bureaucratic patronage. Drawing on comparative political economy approaches, the research demonstrates that despite formal democratic frameworks, informal systems significantly shape governance outcomes. The objective is to identify how institutional weaknesses, elite continuity, and fiscal populism reinforce informality, and to assess the prospects for reform through anti dynasty legislation and civil service improvements. Methodologically, the study integrates qualitative analysis of political networks and informal practices with quantitative insights from fiscal and electoral data across Indonesia, the Philippines, Vietnam, and other Southeast Asian states. Findings reveal that weak bureaucratic systems allow informal networks to dominate service delivery and political access. Political dynasties benefit from institutional voids and economic inequality, consolidating power through electoral dominance and intergenerational succession. Fiscal populism exacerbates these trends by diverting resources toward short term patronage schemes. In contrast, countries like Vietnam, which have pursued fiscal reforms with strong oversight, illustrate pathways for weakening informalism through inclusive, formalized state interventions. The study concludes that while informal institutions remain deeply embedded, targeted reforms such as professionalizing civil service and legislating against dynastic politics can strengthen accountability and institutional performance. Long term success hinges on the alignment of reform efforts with cultural, political, and fiscal realities across Southeast Asia.